2021
DOI: 10.1155/2021/5526713
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Soil and Water Management Measures on Crop Production and Farm Income of Rural Households in the Damota Area Districts, Southern Ethiopia

Abstract: Improving crop productivity and farm income of rural households and ensuring food security through soil and water conservation (SWC) measures are one of the integral parts of sustainable livelihood approaches. The study aims to assess the impact of soil and water conservation measures on improving the rural livelihoods, which is measured in terms of annual crop production and farm income of rural households in the Damota area districts. The data was collected from 378 households (209 adopters and 169 nonadopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It is constructed when stones are available. It protects soil against erosion by trapping sediment and water and improving soil fertility and grain production [ [54] , [55] , [56] ]. Stone face soil bund Stone-faced soil bunds are soil bunds with stone facing on the upstream sides.…”
Section: Methodsmentioning
confidence: 99%
“…It is constructed when stones are available. It protects soil against erosion by trapping sediment and water and improving soil fertility and grain production [ [54] , [55] , [56] ]. Stone face soil bund Stone-faced soil bunds are soil bunds with stone facing on the upstream sides.…”
Section: Methodsmentioning
confidence: 99%
“…The findings showed that across the micro-watersheds, soil loss rates varied significantly by land use/land cover types, with a higher proportion occurring on cropland due to its area coverage and sources of higher rates of erosion in terms of severity. The larger share comes from crop land regions as the severity of soil erosion increases through (0-5) low, (5-10) moderate, (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) high, (20-30) very high, (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) severe, and >40 t/ha/year-extremely severe; nevertheless, the severity proportion is variable among the micro-watersheds. The conclusion suggests that implementing the intended BMP scenarios for croplands could result in positive outcomes to lessen soil losses from the watershed.…”
Section: Model Performance Measurementioning
confidence: 99%
“…Large investments have been made and implemented for conservation of soil and water different parts of Ethiopia [10]. Such investments in physical and agronomic BMP technologies are able to result in the protection of ecosystem services [11]; enhance freshwater availability [12,13]; limit runoff, soil loss, and sediment yields [14][15][16]; improve soil moisture and crop production [17,18]; amend crop yield; improve food security; and improve household incomes [19][20][21]. Despite such efforts to limit runoff, sediment output, or soil Water 2023, 15, 788 2 of 20 erosion, it is challenging to implement improvements because of the growth of agriculture and urban areas [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of the land through soil and water conservation measures has resulted in a change in the structure and type of land [4] and, thus, a significant change in the natural capital of the farmers. Soil and water conservation can improve production conditions, which are beneficial for increasing crop yields and agricultural productivity [9,10], and the increased crop yields and the various received policy subsidies act directly on financial capital. As a productive adaptation behavior, farmers can strengthen their communication and contact with others during the implementation process and expand their social network, which in turn contributes to the improvement of social capital.…”
Section: Impact Of Soil and Water Conservation On Livelihood Capitalmentioning
confidence: 99%
“…Well-being is a multidimensional concept that characterizes the state Sustainability 2023, 15, 6569 2 of 16 and level of human life [7], and improving well-being is the core of sustainable development [8]. A large number of studies have focused on the well-being effect of soil and water conservation, and overall, soil and water conservation improves regional agricultural productivity and has a positive impact on ensuring food security, increasing crop yields and agricultural income [2,9,10], as well as playing a role in mitigating natural disasters, improving the rural industrial structure and raising people's living standards [11,12]. However, existing studies on the well-being effect of soil and water conservation have mainly focused on the contribution of soil and water conservation to society, with limited evidence on the combined well-being effect on actors.…”
Section: Introductionmentioning
confidence: 99%